The influence of printing, lamination and high pressure processing on spot color characterisation - Tomerlin, Renata (Array, 2019)
The food industry has recognized the important role that multi-layered, flexible packaging materials play and it uses them extensively within the packaging processes. Trends within food processing and packaging continuously encourage manufacturers to develop new technologies which extend a product’s shelf-life. The samples that were the subject of research described in this paper are retort stand-up pouches made of multi-layered flexible material, the layers of which have been bonded with a laminating process that aims to both extend a product’s shelf-life and stability, permitting the final processing of the finished product under aggressive regimes. It is intended that packaging, when subjected to graphic reproduction and high pressure processing, shall remain unchanged in all aspects, in particular the visual aspect that is the subject of the research. The samples were printed on polyester film (PET) using a rotogravure printing technique and laminated on aluminum (Al), oriented polyamide (OPA) and finally on inner polypropylene (PP) layers. The sample was monitored for the Vegeta Blue spot colorimetric difference in the CIE L*a*b* space throughout the individual graphic reproduction phases and the final high pressure processing (HPP) of the finished product. The goal is to determine the size of the spot color colorimetric difference (ΔE*) in relation to the defined formula and the established standard. On the basis of measured results, guidelines and recommendations for the correction and quality assessment of spot color reproduction throughout the entire process were defined, with the goal to minimize any deviation to the lowest possible level.